Formation of Trade Relations in the Fergana Valley (1920-1925) - Kayumova Feruzakhon (Universitas Muhammadiyah Sidoarjo, 2022)
The Fergana Valley was the largest, most populous and economically developed part of the Turkestan ASSR, consisting of Kokand, Andijan, Namangan, Margilan and Osh districts. Irrigated agriculture was developed in the Fergana region, and the industry of the region also specialized in the processing of agricultural products [1.1. 41-45 b.]. However, the Fergana Valley did not have ample opportunities for entrepreneurs active in the development of trade.